Whole genome-based phylogenetic analysis of free-living microorganisms. - Fitz-Gibbon, S T (1999)
A phylogenetic 'tree of life' has been constructed based on the observed presence and absence of families of protein-encoding genes observed in 11 complete genomes of free-living microorganisms. Past attempts to reconstruct the evolutionary relation-ships of microorganisms have been limited to sets of genes rather than complete genomes. Despite apparent rampant lateral gene transfer among microorganisms, these results indicate a single robust underlying evolutionary history for these organisms. Broadly, the tree produced is very similar to the small subunit rRNA tree although several additional phylogenetic relationships appear to be resolved, including the relationship of Archaeoglobus to the methanogens studied. This result is in contrast to notions that a robust phylogenetic reconstruction of microorganisms is impossible due to their genomes being composed of an incomprehensible amalgam of genes with complicated histories and suggests that this style of genome-wide phylogenetic analysis could become an important method for studying the ancient diversification of life on Earth. Analyses using informational and operational subsets of the genes showed that this 'tree of life' is not dependent on the phylogenetically more consistent informational genes.